Order and the Virtual The Philosophy and Science of Deleuzian Cosmology - Ross, Bill (Edinburgh University Press, 2024)
Relates the work of Gilles Deleuze to contemporary scienceDemonstrates that Deleuze's philosophy makes a significant contribution to problems in contemporary cosmologyProvides a sophisticated account of the concepts of order and complexity in contemporary cosmology that places them in relation to the history of philosophyShows that Deleuze's conception of the event informs an elaboration of time and space incorporating non-locality in quantum physicsBill Ross demonstrates the relation between Gilles Deleuze's philosophy of difference and the conceptual foundations of contemporary physics through careful engagements with the theory of relativity, quantum physics and chaos and complexity theory. Ross shows that recent work in cosmology by figures such as Lee Smolin and David Bohm calls into question the assumption that the laws of physics are universal and unchanging, a view that Deleuze anticipates. The second law of thermodynamics tells us that order in the universe as a whole is destined to break down. Against this, Ross demonstrates that given Deleuze's conception of the event as an expression of non-locality, and his emphasis on dissymmetry over symmetry, at the cosmological scale the universe is not destined towards disorder: evolution outruns entropy
Description based on online resource; title from PDF title page (publisher's Web site, viewed 03. Jul 2024)
Keywords: Philosophy; PHILOSOPHY / Individual Philosophers